(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The purpose of this research is to investigate the impact that a student’s level of emotional intelligence, locus of control, and religious beliefs have on their ethical behaviour as an accounting student. For the purpose of this study, the sample consists of 175 students who expressed interest in completing the research questionnaire. The Statistical Package for Social Science (SPSS) tests, with the assistance of the IBM SPSS Statistics version, are utilised in the process of hypothesis testing. A number of different regression analysis techniques were utilised in this study, and the findings indicate that the level of religiosity exhibited by auditors has a beneficial impact on the ethical behaviour of auditors. While the locus of control variable of accounting students did not have any impact on ethical behaviour, the emotional intelligence variable does have an impact on the ethical behaviour of students.